Privatization between the necessities of execution and challenges (Al-Mansour Journal, 2022)
Privatization means transferring the ownership of public sector to the level of individuals or that of companies and establishment . The process demands an efficient administration that is achieved by well designed programs appropriate to the nature of the market economics . This is required by the current stage of the economic development in Iraq , a thing that can be executed through the process of privatization . the latter is an essential element of economic development . privatization , to be sure , is needed to reinforce the financial and technical abilities of the economic activities , rebuild establishments , modernize the methods of their work , improve the average of production and combat inflation and unemployment . these important matters , if realized , would set the development process at its best and verify the sustainable development .
Keywords: Privatization; sustainable development; nature of the market economics